Supercharge your Mac with great gear. - Stern, Zack.
4aStill using Mac's original keyboard and mouse--only now they're covered by a thin layer of finger grime? That display starting to look a little dingy and dull? Is your external hard drive running out of room for all your cat photos, or are you interested in stepping up to a network drive so you can access your files from anywhere? Upgrading your Mac's accessories and peripheral is no-brainer--after all, they're such an integral part of the Mac experience. Plus unlike when upgrading internal components, you won't have to dig around inside your Mac's case or fumble with bunch of screws that seems as small as the period at the end of this sentence. Really, the shopping is the hardest part. As always, we're here to make it easier with our picks for the best keyboards, mice, all-in-one printers, display, external hard drives, and network storage. Each category has budget, midrange, and high-end options because as much as we love our Macs, we all still gotta eat.
Keywords: Macintosh (Computer); Keyboards; Computer mice; Printers; External hard drives; Network storages